Abietic acid inhibits UVB-induced MMP-1 expression in human dermal fibroblast cells through PPAR alpha/gamma dual activation - Jeon, Youngsic; Jung, Yujung; Youm, Jong-Kyung; Kang, Ki Sung; Kim, Yong Kee; Kim, Su-Nam (WILEY, 2015)
Peroxisome proliferator-activated receptors (PPARs) are members of the nuclear hormone receptor superfamily of ligand-activated transcription factors and consist of three isotypes: PPAR, PPAR/ and PPAR. PPARs are expressed in various cell types in the skin, including keratinocytes, fibroblasts and infiltrating immune cells. Thus, these receptors are highly studied in dermato-endocrine research, and their ligands are targets for the treatment of various skin disorders, such as photoageing and chronological ageing of skin. Intensive studies have revealed that PPAR/ functions in photoageing and age-related inflammation by regulating matrix metalloproteinases (MMPs) via nuclear factor-kappa B (NF-B) and activator protein-1 (AP-1). However, the detailed mechanism of PPAR/'s role in photoageing has not yet been elucidated. In this study, we confirmed that abietic acid (AA) is a PPAR/ dual ligand and significantly decreased UVB-induced MMP-1 expression by downregulating UVB-induced MAPK signalling and downstream transcription factors, subsequently reducing IB degradation and blocking NF-B p65 nuclear translocation in Hs68 human dermal fibroblast cells. Treatment of cells with AA and GW6471 or bisphenol A diglycidyl ether (BADGE), PPAR or PPAR antagonists, respectively, reversed the effect on UVB-induced MMP-1 expression and inflammatory signalling pathway activation. Taken together, our data suggest that AA acts as a PPAR/ dual activator to inhibit UVB-induced MMP-1 expression and age-related inflammation by suppressing NF-B and the MAPK/AP-1 pathway and can be a useful agent for improving skin photoageing.
Keywords: NF-KAPPA-B; GAMMA; PHOSPHORYLATION; RECEPTORS; RADIATION; INFLAMMATION; MACROPHAGES; ADIPOCYTES; ANTAGONIST